Atypical Multiple Sclerosis – Baló’s Concentric Sclerosis: Two Case Reports and a Review - Popova, E. V.; Bryukhov, V. V.; Boiko, A. N.; Krotenkova, M. V.; Konovalova, O. E.; Sharanova, S. N. (Neuroscience and behavioral physiology, 2018)
We present two case reports of patients with diagnoses of Baló’s concentric sclerosis. The characteristics of the pathogenesis of this disease are considered in relation to the differential diagnosis against other types of multiple sclerosis and potential therapeutic tactics are discussed.